Stakeholder mapping and analysis: Lessons from the strategic approach of a business acceleration for youth project in Malawi - Mzumara, Grace; Ngige, Chris Mwangi; Sheriff, Ramadhan Kadammanja; Slane, David; Chingakule, Oganive; Nkhambule, Emily; Mbewe, Joseph; Phiri, Mercy (2025)
After its third year of implementation, the Business Acceleration for Youth project (BA4Y)1 needed to align its stakeholder engagement efforts to improve implementation, to increase the project’s performance and success. This included improving the project manager’s and team’s understanding of and managing stakeholders more effectively. The project has been framed around a resilience-led sustainability strategy, aiming to strengthen the resilience of youth and women-led business start-ups in nine districts2 of Malawi. The project is providing business incubation and acceleration services3 aimed at developing growth-oriented, sustainable companies that can attract and use investment. Through the provision of industry-specific knowledge, mentorship, access to funding, and customized technical support, the initiative has transformed micro-, small, and medium enterprises (MSMEs) across the country.